The Attachment of Juvenile Mussels via Byssus Weakened by Contaminated Polyethylene Fibers - Wei Ma; Xuelian Wei; Fenglian Zeng; Ming Li; Ping Wang; Yingying Ye; Jiji Li (Toxics)
In the process of mussel farming, the rope for attachment is indispensable, as it provides a stable attachment environment for mussel seedlings, directly affecting their survival rate and growth quality. The objective of this study is to examine the contamination of ropes, composed of polyethylene fibers, by heavy metals and polycyclic aromatic hydrocarbons (PAHs) after three years of deployment and to assess its influence on the attachment and locomotion behaviors of juvenile mussels. Utilizing a laboratory simulation of the seedling wrapping process, a comparative analysis was conducted to evaluate the number of juvenile mussels attached and their movement distances when exposed to contaminated old ropes versus uncontaminated new ropes. The findings indicated that the old ropes markedly diminished the attachment rate of juvenile mussels and heightened their movement distances. In particular, juvenile mussels utilizing old ropes exhibited a final attachment rate of 15.0% and an average movement distance of 0.86 cm, whereas those using new ropes achieved a final attachment rate of 96.7% with an average movement distance of 0.26 cm. Further inspection found that heavy metals and PAHs were present in the old rope, among which the concentrations of Zn (17.127 μg/g) and Pb (22.905 μg/g) in heavy metals were high, and the concentrations of Phe (5.53 μg/kg), Fla (6.35 μg/kg), and Pyr (5.17 μg/kg) in PAHs exceeded the detection limits, which were the main source of pollution. This research underscores the potential risk that heavy metal and PAHs contamination pose to the health of juvenile mussels and the profitability of aquaculture, emphasizing the critical need for the regular replacement of clean ropes.